(untitled) (Fiep Bulletin - online, 2011)
In the modern history of Western civilization colonization of the system calls made by the dominant nations is a process of ranking and socio-cultural arbitrary, which resulted in a stratification and classification of "civilized" societies. This concept of civilization is based on a hegemonic common reference to the period from the sixteenth to eighteenth century, which represented the ideology reflected in colonizing Eurocentric version of knowledge, especially in relation to the colonized peoples in the production of knowledge rated the subordinate, as in the African Diaspora. The aim of the study was to assess the extent to which Capoeira could be an artifact of the African Diaspora, in order to characterize it as a cohesive identity in school. At first, the theoretical foundation of the study is anchored in a literature review on the conceptual aspects of the African Diaspora, and history of Capoeira, and then make parallels between it and the construction of identity in school. We conclude that the Capoeira, groups of poultry with its statutes and graduations, new teaching methodologies affirming new identities in school, and constructing identities of resistance, advancing the recognition and appreciation of the roles of blacks in Brazilian society, to the point of becomes Intangible Brazilian.